2017
DOI: 10.1039/c7tc02775c
|View full text |Cite
|
Sign up to set email alerts
|

Controlling crystallization to imprint nanophotonic structures into halide perovskites using soft lithography

Abstract: Nanophotonic patterns are imprinted into halide perovskite films using polymer stamps and a solvent mixture to control the perovskite's crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 35 publications
0
68
0
Order By: Relevance
“…During this process, a large number of small crystals generate slowly with volatilized solvent (at 50 °C). Then the perovskite grains migrate and recrystallize to form large crystals (at 100 °C) and achieve good crystalline within the spatial confinement . Besides, high‐resolution, cross‐sectional scanning electron microscopy (SEM) images and energy dispersive X‐ray (EDX) spectrum of the nanowire arrays prepared on indium tin oxide substrates further confirm that no perovskite is left between the nanowires (Figure S3, Supporting Information) …”
Section: Resultsmentioning
confidence: 81%
“…During this process, a large number of small crystals generate slowly with volatilized solvent (at 50 °C). Then the perovskite grains migrate and recrystallize to form large crystals (at 100 °C) and achieve good crystalline within the spatial confinement . Besides, high‐resolution, cross‐sectional scanning electron microscopy (SEM) images and energy dispersive X‐ray (EDX) spectrum of the nanowire arrays prepared on indium tin oxide substrates further confirm that no perovskite is left between the nanowires (Figure S3, Supporting Information) …”
Section: Resultsmentioning
confidence: 81%
“…As demonstrated by other groups, a front-side textured architecture can be realised with nanoimprint processes. [26][27][28] Paetzold and coworkers demonstrated that pattering the front surface does not affect Table 1. LiF 107 ITO 80 SnO 2 5 PCBM 15 perovskite 333 NiO 10 ITO 20 n + a-Si:H 8 i a-Si:H 5 Table 1 The thicknesses of the layers in our simulated tandem cell.…”
Section: Simulated Tandem Cell Architecturesmentioning
confidence: 99%
“…The resulting patterned perovskite grating film (Figure b) was integrated in parallel‐type photodetector arrays, exhibiting respectable photocurrent switching properties in the visible regime (Figure c). Afterward, Garnett et al improved this method by using DMF&DMSO mixed solvents . The low‐ T b ( = 153 °C) solvent, DMF, evaporated rapidly from the perovskite thin film during preannealing, resulting in supersaturation of the perovskite precursor and triggering homogeneous nucleation.…”
Section: Direct Patterning Technologymentioning
confidence: 99%